2016
DOI: 10.4103/0972-124x.168485
|View full text |Cite
|
Sign up to set email alerts
|

Profilometric analysis of root surfaces after using various polishing agents

Abstract: Background:Polishing is an important step in oral prophylaxis procedure which retards further accumulation of plaque on the root surfaces. Though polishing was done with various abrasive particles with different sizes over a long period of time, it was never been highlighted to evaluate the ideal polishing material and the particle size that would produce the ideal surface smoothness (Ra <0.2 μm).Materials and Methods:The present study was carried out on 70 periodontally involved, caries-free extracted human t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Application of a prophy paste onto the tooth surface using a nylon bristle brush or rubber prophy cup as part of the mechanical periodontal treatment is the most widely used among the various polishing procedures. Polishing as the final step is believed to reduce surface roughness and remove stains and biofilm [17][18][19]. Some information is available regarding surface shifts of restorative materials after polishing procedures [20,21] and the effects of air polishers on tooth surfaces [22,23], but little attention has been paid to the comparison of rubber prophy cups and nylon bristle brushes.…”
Section: Introductionmentioning
confidence: 99%
“…Application of a prophy paste onto the tooth surface using a nylon bristle brush or rubber prophy cup as part of the mechanical periodontal treatment is the most widely used among the various polishing procedures. Polishing as the final step is believed to reduce surface roughness and remove stains and biofilm [17][18][19]. Some information is available regarding surface shifts of restorative materials after polishing procedures [20,21] and the effects of air polishers on tooth surfaces [22,23], but little attention has been paid to the comparison of rubber prophy cups and nylon bristle brushes.…”
Section: Introductionmentioning
confidence: 99%
“…These factors all exacerbate the wear of cementum. Jana et al ( 2016 ) used sandblasted particles of different sizes and compositions to polish teeth in vitro after scaling and finally found that only 3–5 μm hydroxyapatite crystals could decrease the surface roughness of sandblasted teeth reach Ra = 0.2 μm. For other particles, the size needed to be less than 1 µm to achieve the desired postblast roughness (Jana et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is a widespread debate about whether the tooth surface should be polished or not. Some studies suggested that polishing removes plaque and reduces bacterial colonization, resulting in a smooth tooth surface (17,18). The results of the present study revealed alteration of the enamel surface with all the prophylactic methods applied.…”
Section: Discussionmentioning
confidence: 99%